Risk Analysis of Groundwater Contaminant in Rural Areas Using Spatial Distribution - Herawati Herawati; Maria Kanan; Anwar Mallongi; Ramli Bidullah; Sandy N. Sakati; Dwi Wahyu Balebu (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Background: Water is a very important material for the life of creatures in nature and its function for life cannot be replaced by other compounds. Groundwater is an important resource for humans, especially in rural areas that depend on Groundwaters as the main source of clean water. However, the quality of groundwater in many areas has decreased due to pollution from human activities, such as agriculture and industry. Method: This study aims to analyse the level of pollution risk of groundwaters in rural areas of Masama District, Banggai Regency using descriptive quantitative methods. Spatial analysis of pollution risk was conducted on 516 Groundwaters selected as samples. Spatial data is collected by recording the location of each well using GPS, which is then used to create a spatial map. The pollution risk analysis is based on the Sanitation Inspection results, using 11 key indicators. Result: The results showed that 4 Groundwaters (0.78%) were in the very high pollution risk category, 115 Groundwaters (22.29%) were in the high-risk category, 204 Groundwaters (39.53%) were classified as medium risk, and 193 Groundwaters (37.40%) had low pollution risk. The results indicate that most Groundwaters in the study area are at moderate to high risk. Groundwaters with high and very high risk are dominated by Groundwaters located in Minang Andala, Purwo Agung and Kembang Merta villages, which are agricultural areas with sufficient area and most of the people have livestock around their homes which could potentially be a source of contaminants. Conclusion: This study shows that the majority of Groundwaters in the study area have a moderate to high risk of pollution, with high and very high-risk categories found in villages that have agricultural and livestock activities. This emphasises the need for more intensive groundwater management and protection measures.